If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4x+6)-(3x+1)=
We move all terms to the left:
(4x+6)-(3x+1)-()=0
We add all the numbers together, and all the variables
(4x+6)-(3x+1)=0
We get rid of parentheses
4x-3x+6-1=0
We add all the numbers together, and all the variables
x+5=0
We move all terms containing x to the left, all other terms to the right
x=-5
| (1/5)-3b=5 | | 5=t3 | | 5n+65n=37n | | 7y^2=28. | | 6(2-d)=9(-d4) | | -2.5x-4.25x=35.1 | | D(2D+4)y=0 | | -3(2x+4)=9 | | 4x(x^2+2)=9 | | -8(5x-4)+8=5x | | 0.01x+0.1(x+20,000)=2220 | | -8(5x-4)+8=5x | | 601/12.9=1250/n | | 5n+4+3n=36 | | {4}{3}x{1}{3}=x+7 | | -3x+7-2x=52 | | (2x+3x)+62=180 | | (x+5)(x-2=0 | | D=(m-64)2 | | 0.3x+2=5.6 | | 7t-21=2t-18+2R | | t1=2(1)+4 | | -14-n=-22 | | 5e+6=-6 | | 2(8x—7)+8=-54 | | 2(8x—7)+8=—54 | | 5(2x+1)=27 | | -4=-10+v | | 3x+2=12∴x= | | 11x+9x=16 | | (x/2)+(6x/7)=19/14 | | -60=3(1-3x) |